Killing Him Just Made Him Stronger: On Herod's Speculation in Matt 14:1–2 that Jesus was John Resurrected - Harriman, K. R. (Neotestamentica, 2024)
All the Synoptic Gospels record a peculiar claim in a story about Herod, wherein it is said that Jesus is John the Baptist risen from the dead. Obviously, none of the Gospel authors agree with this claim, which raises the question of why they recorded it. With a focus on Matthew, I argue that this claim appears for two reasons: 1) the resurrection speculation presents perhaps the most dramatic—even if misinformed—statement of Jesus's continuity with John as well as his superiority; 2) the resurrection speculation provides an ironic foreshadowing of the link between Jesus's identity and his fate, a link that fits with the author's themes of resurrection theology. To make this argument, I first perform a pericope comparison between Matthew's version and the other Synoptics. Then I examine the place of the text in Matthew's overall presentation of the relationship of Jesus and John. Finally, I explore how this text relates to the theology of resurrection presented in Matthew.